Determination of Some Environmental Conditions as a Risk Factors for Prevalence of Type 2 Diabetes Mellitus by Using Biochemical and Hematological Parameters - Al-nada Ali Kanaem Al-ibady, Qater (Al-Kufa University Journal for Biology, 2019)
The present study was carried out to determine the environmental conditions as a risk factors to determination and prevalence type two diabetes by many methods such as biochemical and haematological parameters. 65 patient (42 males and 23 females) of ages between 35-90 years old, were taken from diabetic centre in Baghdad province. In this study there are high significant differences for the males and females, therefore LSD-value was 24.88**. And LSD-value for HDL was 7.833**, also this study recorded high significant differences for the relationship between the age and attack with type two diabetes mellitus, then the LSD-value were 33.90**.This study recorded high significant differences for the relationship between the smoking patients and this disease . The LSD-value were 25.96**. Generally, this study recorded relationship between the diabetes and overweight, then LSD-value were 44.28**. Also the relationship between theCholesterol and Triglyceride was high significant and the P-value was 0.54**, and the relationship of Cholesterol with LDL was high significant, then the P-value was 0.75**, but the relationship between the Cholesterol and VLDL, also there are high significant differences, then the P-value was 0.39**. This study also recorded high significant for the relationship between Triglyceride and HDL and equal 0.32**. But the relationship between the Triglyceride and VLDL was high significant differences, then the P-value equal 0.74**. Also the relationship between the HDL and VLDL was high significant differences and equal 0.34** under the (p<0.01) and (p<0.05).While conclusions ofcurrent study are recording high significant of the relationship for gender, age groups, smoking, cholesterol, Glucose, and triglyceride,HDL and weight for people whoseattack with diabetes.Therefore the aims of current study are determining some risk factors that affects by some environmental conditions which possible to associate in developing complication for individuals with diabetes type 2. By using some testes to indicate the incidence of diabetes mellitus type 2, either by using the appropriate therapy or modulating some environmental conditionsin the future, which can causative these potential risk factors.